The leaf sheath promotes prolonged flooding protection by giving rise to specialized adventitious roots. Issue 4 (11th March 2023) - Maric, Aida; Hartman, Sjon
Abstract : This article is a Commentary on Lin et al . (2023), 238 : 1403–1419 .